Pengenalan Sifat dan Karakteristik Tabung dengan Pendekatan Matematika Realistik - Desi Ariani; Cut Morina Zubainur; M. Duskri (Didaktik Matematika, 2016)
The learning process of mathematics, especially the one related to the characteristic of cylinder, at elementary school or at the other higher level of school only required the students to memorize the concept of it without comprehending its meaning. Based on that reason, it is a need to have an appropriate learning approach to help the students in understanding the characteristics of cylinder. This research aims to describe the learning activity of cylinder characteristic by using Realistic Mathematics Education (RME). There were five students of grade V from SDN 3 Sigli who were involved in this study.Byusing the approach, the students were motivated to learn about cylinder characteristics more meaningfully. The use of the appropriate context that matches with the students culture also became a strong foundation for them in possessing a meaningful experience toward the material. It also can lead them to have more formal learning experiences (identifying the characteristics of cylinder). There were three kinds of activities that are conducted in the study and were related to introduction the characteristicsof cylinder. They were glueing by using different colour, drawing a tissue place, and unloading the model of the tissue place. The use of concrete objects that relates to the culture of the students to develop their ability in understanding the material of the cylinder was the first step in learning the cylinder volume concept